The Developmental Mechanism of Integration Punnasikkha into Happiness Multicultural Society for the Elderly in Kalasin Province - Kaewsaeng, Khwanjai; (Samai Hasook), Phrakhru Dhammabhisamai; Sopajorn, Warinee; Kaewmat, Orawan (Dhammathas Academic Journal, 2024)
The purposes of this research were 1) to study the condition and factors affecting the integration of merit and multicultural society creating happiness for the elderly in Kalasin Province; 2) to develop a mechanism for developing the integration of merit and multicultural society creating happiness for the elderly in Kalasin Province; and 3) to evaluate the mechanism for developing the integration of merit and multicultural society creating happiness for the elderly in Kalasin Province. Research is a mixture of qualitative research. The sample group used in this research consisted of 387 elderly people living in the Mueang District of Kalasin Province, 13 key informants in structured interviews, and 9 experts. Tools used in the research included structured interviews, a questionnaire about conditions and factors affecting the integration of merit and multicultural society to create happiness for the elderly. The collected data were analyzed using a ready-made program; correlation coefficients Pearson, and a stepwise multiple regression analysis. The research results found that: 1. A multicultural society of the elderly had a positive relationship with the merit of the elderly (donations, precepts, and meditation) at a low level with statistical significance. The multicultural society of the elderly has a positive relationship with the society that creates happiness for the elderly at a moderate level. When considering each aspect, it was found that the aspect of comfort and the aspect of happiness were at a moderate level. And happiness and elegance were at a low level with statistical significance. 2. Bunyasikkha had a positive relationship with the society that creates happiness for the elderly at a low level, especially the precepts and pray/meditation were at a low level with statistical significance level of 01. While considering each aspect, it was found that 1) the precepts aspect had a positive relationship with a society that creates happiness in terms of happiness and elegance and 2) the aspect of meditation had a positive relationship with a society that creates happiness at a low level with statistical significance. 3. Constructing a multiple regression found that society creating happiness for the elderly varies according to a multicultural society in 3 aspects, namely mental, physical, and social, and together they can predict correctly (R2 = 22.80%).